KEFEKTIVAN MEDIA PUZAWA BERMUATAN KARAKTER CINTA TANAH AIR PADA PEMBELAJARAN MEMBACA AKSARA JAWA DI SEKOLAH DASAR - Yayuk Purwanti; Fardani, Much Arsyad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low reading skills of Javanese script of fifth grade students at Pati. Wetan 03 Public Elementary School as seen from the results of observations and interviews that have been given to teachers and students. The purpose of this study is to explain the effectiveness of PUZAWA media containing the character of love for the homeland on Javanese script reading skills. This research was conducted at Pati Wetan 03 Public Elementary School. The type of research used is quantitative experiment with One group pretest posttest design. Data collection techniques used are observation, interviews, and tests. While the data analysis techniques used are normality test and paired sample t test. The results of this study indicate that the paired sample t test obtained a significant value (2-tailed) from this study is 0.000 (p <0.05). Supported by an increase in pretest posttest values showing that the media used is effective for learning to read Javanese script.